2021
DOI: 10.1101/2021.03.22.21254139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Brain Ischemia, Infarction and Hemorrhage in Subjects Dying with or Without Autopsy-Proven Acute Pneumonia

Abstract: Stroke is one of the most serious complications of Covid-19 disease but it is still unclear whether stroke is more common with Covid-19 pneumonia as compared to non-Covid-19 pneumonia. We investigated the concurrence rate of autopsy-confirmed acute brain ischemia, acute brain infarction and acute brain hemorrhage with autopsy-proven acute non-Covid pneumonia in consecutive autopsies in the Arizona Study of Aging and Neurodegenerative Disorders (AZSAND), a longitudinal clinicopathological study of normal aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
3
0
1
Order By: Relevance
“…An important issue is whether or not COVID-19 lower respiratory disease elicits more intense systemic repercussions than typical acute pneumonia. Our investigations ( 112 , 156 , 162 ) indicate that acute or subacute ischemic changes, infarctions or hemorrhages are probably not more common in COVID-19 than they are in subjects dying without COVID-19 or with or without non-COVID-19 acute pneumonia. Early adoption of low molecular weight heparin therapy may have reduced thromboembolism in our study subjects, in comparison with COVID-19 decedents in the first few months of the pandemic.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…An important issue is whether or not COVID-19 lower respiratory disease elicits more intense systemic repercussions than typical acute pneumonia. Our investigations ( 112 , 156 , 162 ) indicate that acute or subacute ischemic changes, infarctions or hemorrhages are probably not more common in COVID-19 than they are in subjects dying without COVID-19 or with or without non-COVID-19 acute pneumonia. Early adoption of low molecular weight heparin therapy may have reduced thromboembolism in our study subjects, in comparison with COVID-19 decedents in the first few months of the pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…Microvascular, acute and subacute ischemic, and/or hemorrhagic lesions ( 4 , 11 , 13 , 20 , 26 , 30 , 33 , 35 , 36 , 38 , 39 , 45–50 , 53–62 ) have frequently been reported in COVID-19 but these are also common in unselected autopsy series. We found that acute and subacute ischemia, infarction, and hemorrhage were present in the brains of up to 14% of 691 consecutive pre-COVID-19 autopsies with or without concurrent autopsy-proven pneumonia ( 162 ). In comparison, in reviews of COVID-19 publications, reported clinically determined rates of acute brain infarction or hemorrhage range from 0.5% to 20% ( 1 , 4 , 5 , 13 , 25 , 26 , 28 , 29 , 32 , 34–36 , 38 , 39 , 45–48 , 53–55 , 156 , 163–175 ).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure in COVID-19 certainly worsens the initial status of the patient but may be associated with other pulmonary diseases. The study by Beach et al aimed at comparing the incidence of ischemic and hemorrhagic stroke in patients with pneumonia and COVID-19 with that of ACVA in other pneumonias not associated with COVID-19 showed a similar risk of ACVA in patients of both groups [33]. The role of associated coagulopathies cannot be excluded.…”
Section: Ischemic Stroke In Covid-19mentioning
confidence: 99%
“…Одною з локацій взаємодії вірусу SARS-CoV-2 з ACE2 є нюховий епітелій в носовій порожнині з наступним проникненням вірусу через ґратчасту пластинку біля нюхової цибулини, що спостерігається при ізольованій аносмії чи агевзії з респіраторними симптомами або без них [27,28]. На думку науковців з Національного інституту США з проблем старіння пряме інфікування нейронів головного мозку вірусом SARS-CoV-2 є вкрай рідкісним явищем, тоді як більшість неврологічних наслідків може бути наслідком сепсису, коагулопатії, гіперімунної реакції або поліорганної недостатності [29].…”
Section: вступunclassified